Modified Maxillary-Swing Approach for Resection of Primary Malignancies in the Pterygopalatine Fossa - Xie, Li; Huang, Wenxiao; Wang, Junqi; Zhou, Yue; Chen, Jie; Chen, Xue (Frontiers in Oncology, 2020)
Background En bloc resection of malignancies in the pterygopalatine fossa (PPF) poses critical challenges. Using the modified maxillary-swing (MMS) approach, we achieved monobloc removal of primary malignancies in this region. This study provides a detailed account of the surgical techniques and indications used. Methods We enrolled seven patients with primary malignancies in the PPF during a period from January 2012 to January 2019 in this retrospective study. After malignancies were confirmed by biopsy as well as evaluation with computed tomography (CT) and magnetic resonance imaging (MRI) scans, all of the patients underwent MMS surgery under general anesthesia to extirpate these tumors. We performed regular postoperative follow-up using CT and MRI scans. Results En bloc resection was successfully performed in all cases. We observed negative margins in six cases and positive margins in one patient with adenoid cystic carcinoma, who received postoperative radiotherapy. The most common complication was facial numbness. During the follow-up period (range, 6–69 months), one patient suffered from recurrence, while the others did not. Conclusion The advantages of the MMS include a wide surgical field, full exposure, and easy manipulation. We expect this approach to become an alternative to the monobloc resection of malignancies in the PPF that involve the infratemporal fossa, maxillary sinus, nasal cavity, orbit, or oral cavity.